1991
DOI: 10.2307/40285521
|View full text |Cite
|
Sign up to set email alerts
|

A New Illusion of Time Perception

Abstract: When two very short time intervals are presented serially by sound markers (in such a way that they share a common marker) the subject's duration judgments of the second time interval can be affected by the duration of the first interval. Such a conspicuous effect has not been reported in the literature. Standard empty time intervals of 120, 240, 480, and 720 msec were preceded by a neighboring empty time interval of various physical durations, and subjects adjusted a comparison empty time interval to the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 27 publications
8
52
0
Order By: Relevance
“…Because in our experiment we asked participants to compare crossmodally-defined empty intervals to filled auditory intervals, we have been able to limit the influence of possible biases such as temporal shrinking (Nakajima et al, 1991cited in Nakajima et al, 2004Sasaki et al, 2002), temporal stretching (Sasaki et al, 2010), and temporal ventriloquism effects (Morein-Zamir, 2003). The psychophysical findings on duration perception of crossmodally-defined intervals in our study are overall consistent with previous work (i.e., Grondin & Rousseau, 1991).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Because in our experiment we asked participants to compare crossmodally-defined empty intervals to filled auditory intervals, we have been able to limit the influence of possible biases such as temporal shrinking (Nakajima et al, 1991cited in Nakajima et al, 2004Sasaki et al, 2002), temporal stretching (Sasaki et al, 2010), and temporal ventriloquism effects (Morein-Zamir, 2003). The psychophysical findings on duration perception of crossmodally-defined intervals in our study are overall consistent with previous work (i.e., Grondin & Rousseau, 1991).…”
Section: Discussionsupporting
confidence: 82%
“…The filled interval was a continuous sound that lasted for 30%, 60%, 80%, 100%, 120%, 140%, and 170% of the duration of the empty interval. We used the combination of empty and filled intervals within a trial to control for perceptual time perception biases such as temporal shrinking (Nakajima, ten Hoopen, & van der Wilk, 1991cited in Nakajima et al, 2004Sasaki, Suetomi, Nakajima, & ten Hoopen, 2002), temporal stretching (Sasaki et al, 2010) or temporal ventriloquism (Morein-Zamir, 2003) which were likely to occur if we had asked participants to compare two empty intervals. Temporal shrinking refers to a perceptual bias that occurs when a train of three or four brief signals are presented.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, subsequent research illustrates significant differences in associative memory tasks involving four note sequences of percussive and flat tones (Schutz & Stefanucci, 2010), as well as differences in the duration judgment strategies employed when estimating their length (Vallet, Shore, & Schutz, 2014). Although this work was not published in Music Perception, this journal has published other work on associative memory (Boltz, 2001) as well as duration estimation (Nakajima, Hoopen, & Van Der Wilk, 1991). Consequently, we believe envelope's crucial role in a variety of tasks focused on ostensibly unrelated issues is broadly relevant for those interested in the perception of music (as well as sound in general).…”
Section: Amplitude Envelope Explains a Perceptual Paradoxmentioning
confidence: 94%
“…Other studies (Miyauchi & Nakajima, 2005;Nakajima et al, 2004;Nakajima, ten Hoopen, & van der Wilk, 1991;ten Hoopen, Miyauchi, & Nakajima, 2008) have reported that a time interval that is immediately preceded or followed by another, shorter time interval is perceived as being shorter (the temporal assimilation effect). Because the onset-onset interval between two neighboring tone bursts in the present study was 40 msec at 25 Hz, the test interval (100 to 700 msec) might be perceived as being shorter due to the temporal assimilation effect.…”
Section: Discussionmentioning
confidence: 99%